KARAKTERISASI MINYAK BIJI LABU KUNING (Cucurbita pepo L.) HASIL EKSTRAKSI DENGAN ALAT SOXHLET - Abdillah, Muhammad Nur (JURNAL FARMASI GALENIKA, 2014)
Vegetable oil that produced from pumpkin seed can be used to be a raw material of industrial manufacture such as foods, cosmetics and pharmaceutical industries. The aim of this research is to characterize the physical and chemical properties of pumpkin seed oil extracted using Soxhlet apparatus. This research hopefully can give the information about the quality of pumpkin seed oil from Soxhlet apparatus extraction so that the data can be used on the next research. Characteristics of pumpkin seed oil (Cucurbita pepo L.) from Soxhlet apparatus extraction had been researched by identified the parameter of physical properties such as color by chromameter, boiled and smoke points, specific gravity by picnometer, refractive index by refractometer, water content, and impurities; chemical properties such as acid value, peroxide value, iodine value, saponification value; functional groups by Fourier Transform Infrared (FTIR). Rendemen of the extraction was 35,35(±2,8)% at 60oC for 4-6 hours. The physical properties were: color: the value of L: 52,79(±5,09), a: +2,86(±2,22), b: +26,04(±0,70); smoke point: 119,50(±0,70)oC, boiling point: 209,00(±4,24)oC; specific gravity 0,92(±8,23x10-4); refractive index 1,46(±8,21x10-4) at 25,85(±0,05)oC; water content 8,85(±0,76)%; impurities 11,74(±0,34)%; and the chemical properties were: acid value 2,76(±0,24) mg KOH/g; peroxide value: 49,56(±8,99)meq/1000g and 24,78(±4,50)mmol/1000g; iodium value 13,38(±1,47)mg I2/100g; saponification value  357,94(±62,97)mg KOH/g; has the specific stretching ethylenic groups at 3007cm-1 andasymetric stretching of ester carbonyl groups -C=O at 1745-1659cm-1, also asymetric stretching of ester C-O-C at 1235-1105cm-1 and bending of ester O-C-O at 592cm-1 on fingerprint region.